Associations of the gut microbiome and clinical factors with acute GVHD in allogeneic HSCT recipients - Ilett, Emma E. (Blood Adv, 2020)
Acute graft-versus-host disease (aGVHD) is a leading cause of transplantation-related mortality after allogeneic hematopoietic stem cell transplantation (aHSCT). 16S ribosomal RNA (16S rRNA) gene-based studies have reported that lower gut bacterial diversity and the relative abundance of certain bacteria after aHSCT are associated with aGVHD. Using shotgun metagenomic sequencing and a large cohort, we aimed to confirm and extend these observations. Adult aHSCT recipients with stool samples collected from day −30 to day 100 relative to aHSCT were included. One sample was selected per patient per period (pre-aHSCT (day −30 to day 0), early post-aHSCT (day 1 to day 28), and late post-aHSCT (day 29 to day 100)), resulting in 150 aHSCT recipients and 259 samples. Microbial and clinical factors were tested for differences between time periods and an association with subsequent aGVHD. Patients showed a decline in gut bacterial diversity posttransplant, with several patients developing a dominance of Enterococcus. A total of 36 recipients developed aGVHD at a median of 34 days (interquartile range, 26-50 days) post-aHSCT. Lower microbial gene richness (P = .02), a lower abundance of the genus Blautia (P = .05), and a lower abundance of Akkermansia muciniphila (P = .01) early post-aHSCT was observed in those who developed aGVHD. Myeloablative conditioning was associated with aGVHD along with a reduction in gene richness and abundance of Blautia and A muciniphila. These results confirm low diversity and Blautia being associated with aGVHD. Crucially, we add that pretransplant conditioning is associated with changes in gut microbiota. Investigations are warranted to determine the interplay of gut microbiota and conditioning in the development of aGVHD.